Intiḫāb-i kulliyāt-i Ātiš - Ātiš Lakhnawī, Ḫwāǧa Ḥaidar ʿAlī,Jāved, Aḥmad (Dāniš Pablišing Kampanī, 2004)
Selected ghazals of an Urdu poet
Ghazals - In arab. Schrift, Urdu. - Mit Nebent. in lateinischer Schrift
Keywords: Urdu; Ghasel